Análisis de la agudeza visual y sensibilidad al contraste en técnicas de cirugía refractiva lasik: revisión bibliográfica - Reinoso Rojas, Anyela Rosa (Universidad Antonio Nariño, 2021)
Optometry is an area of ​​health that cannot be separated from refractive surgery techniques. By which this becomes a main element to contribute to the well-being of each of the patients at the level of their visual quality. The World Health Organization (WHO) in the first global vision report published in 2019, specifies that at least 2.2 billion people have a visual deficiency or blindness; of which more than 1 billion of these had been avoided or treated. One of the main causes of increased visual deficiency is refractive errors, being the main cause of attention at the optometric and ophthalmological level. Currently, various treatments are used to correct and remedy visual defects that suffer or begin to affect people during their lives, as these are quite annoying. Refractive surgery, is one of the options that patients have to recover an important function such as visual acuity, it is applied from ophthalmology, to improve refractive problems and give patients the possibility of obtaining a better visual health. By virtue of this, for this reason, the present work aims to carry out a bibliographic review on the alterations of visual acuity and contrast sensitivity existing in LASIK refractive surgery, in order to describe them and give a comparison of these two variables used in the professional optometric practice.